Guide to international transfer pricing : law, tax planning and compliance strategies / general editors, Duff & Phelps, A. Michael Heimert, Michelle Johnson. - Heimert, A. Michael; Johnson, Michelle, (Economist).; Duff & Phelps Corp. (Alphen aan den Rijn, The Netherlands : Kluwer Law International, 2013)
The pricing of goods and services within a multi-divisional organization, particularly in regard to cross-border transactions, has emerged as one of the most contentious areas of international tax law. This is due in no small measure to the rise of transfer pricing regulations as governments seek to stem the flow of tax revenue overseas, making the issue one of great importance to multinational corporations. This thoroughly practical work provides guidance on an array of critical transfer pricing issues. The guide's relevance is further enhanced by the inclusion of 14 country chapters covering domestic transfer pricing issues in a variety of key national jurisdictions.
Includes bibliographical references and index.
Keywords: Transfer pricing -- Taxation -- Law and legislation; International business enterprises -- Taxation -- Law and legislation